(untitled) (Conferencea, 2024)
In the article, in livestock farms specializing in dairy farming in our Republic, purebred cows have their hooves cleaned and trimmed, then bathed in 5% formalin, hydrocortisone 4ml, 0.5% novocaine 5ml intramuscularly, cal-bor-mag (250 ml intravenously every 24 hours times in total three times), phenylbutazone-20 (5 ml intravenously for 100 kg body weight once every 48 hours for a total of three times) reduced inflammatory processes, increased regeneration processes and increased the number of erythrocytes in the blood by 18.4%, the amount of hemoglobin It is reported to increase by 8.5%, decrease the number of leukocytes by 15.8%, and decrease the erythrocyte sedimentation rate by 27.2%.